A 9 × 9 matrix representation of Temperley-Lieb algebra and corresponding entanglement - 苟立丹 朱瑞晗 (Chinese physics B, 2012)
We present the matrix U. The 9 × 9 U matrix is a representation of specialized Temperley-Lieb algebra. Based on which, a unitary R matrix is generated via the Yang-Baxterization approach. The 9 × 9 R matrix, a solution of the Yang-Baxter equation, is universal for quantum entanglement.